Blending Cylinders and Cones using Canal Surfaces - Kazakevičiūtė, M.; Krasauskas, R. (Nonlinear Analysis: Modelling and Control, 2000)
There is reviewed the construction of a rational blending surface between cylinders and cones in some interlocation cases. This surface is constructed as a patch of rolling ball envelope, i.e. as a patch of tangent canal surface of rational-variable radius. This construction defines rational parameterization of a blending surface. The constructed surface is Laguerre invariant.
Keywords: none